Petrographic analysis of in-service cementitious mortar subject to freeze-thaw cycles and deicers - Qiao, Chunyu; Chen, Xu; Suraneni, Prannoy; Weiss, W. Jason; Rothstein, David (Cement & concrete composites, 2021)
Chloride-based deicers, especially CaCl2 and MgCl2, can damage cementitious materials due to the formation of mineral phases such as calcium oxychloride and brucite. However, there are only limited direct observations of calcium oxychloride formed in cementitious materials in the field. This paper uses petrographic methods to evaluate damage of an in-service cementitious mortar substrate subject to freeze-thaw cycles and deicers for six years. The amount of calcium hydroxide in the mortar was quantified using thermogravimetric analysis. Changes in hydration products and microstructure were characterized by optical microscopy. Scanning electron microscopy coupled with energy dispersive X-ray spectroscopy was used to examine the morphology and elemental composition of secondary deposits related to the deicer damage. The mortar with less than 3% air exhibits horizontal cracks and microcracks cutting around aggregate particles. The cracks and microcracks are partially filled with calcium oxychloride due to the application of CaCl2. A densified crust of brucite and calcite, likely associated with the usage of MgCl2, covers the top surface of the damaged mortar. The deicer exposure results in leaching of calcium hydroxide mainly due to the formation of calcium oxychloride. Calcium leaching increases the apparent paste porosity in the damaged mortar, which likely weakens the physicomechanical properties of the mortar and accelerates the ingress of external deicer solutions. Moreover, the deicer application results in air-void-filling by calcium oxychloride and secondary ettringite, which may reduce the space available to release the internal stresses associated with ice formation and thus compromises the freeze-thaw durability.